1993
DOI: 10.1103/physrevlett.71.3485
|View full text |Cite
|
Sign up to set email alerts
|

Buckled crystalline structure of mixed ionic salts

Abstract: X-ray absorption fine structure (XAFS) measurements of mixed salts Rb^Ki-ccBr and RbBr^Cli-y at their congruent melting points compositions reveal that their actual structure buckles about the NaCl average structure with an rms angular deviation from collinearity of 7°-9°. XAFS measures the buckling directly through three-body correlations, and verifies the homogeneity and randomness of the mixtures. The characteristic ionic sizes are found to be dependent on concentration, causing changes to 0.1 A in interato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 13 publications
7
42
0
Order By: Relevance
“…Although experimental phases and amplitudes can be favorable over theoretical phases for the first one or two SS shells, 21 naturally they cannot be employed for EXAFS fits out to distances larger than ∼3.0 Å depending on the structure. Several applications of FEFF phases and amplitudes to "real" systems have been reported where all significant scattering paths with an amplitude weight of more than ∼3% out to distances of ∼6 Å were included in the analysis, confirming the reliability of theoretical EXAFS calculations [22][23][24][25] (here "real" refers to systems other than pure metals).…”
Section: Resultsmentioning
confidence: 79%
“…Although experimental phases and amplitudes can be favorable over theoretical phases for the first one or two SS shells, 21 naturally they cannot be employed for EXAFS fits out to distances larger than ∼3.0 Å depending on the structure. Several applications of FEFF phases and amplitudes to "real" systems have been reported where all significant scattering paths with an amplitude weight of more than ∼3% out to distances of ∼6 Å were included in the analysis, confirming the reliability of theoretical EXAFS calculations [22][23][24][25] (here "real" refers to systems other than pure metals).…”
Section: Resultsmentioning
confidence: 79%
“…The details of the techniques using these x-ray spectroscopy methods to study local structure of materials can be found in Refs. [25][26][27][28][29][30][31][32]. XANES experiments ͑beamline X11A at NSLS͒ were mainly focused on the Ti K edge to examine its possible off-center displacement while the EXAFS data were collected for all three cations ͑K edge of Cu, Ti at beamline X11A and Ca at beamline X15B, NSLS͒ to measure the cation short-range order.…”
Section: B Synchrotron X-ray Diffractionmentioning
confidence: 99%
“…A recently published synchrotron X-ray diffraction study 11 12,17 . In the current work, we report results obtained by extending the X-ray absorption measurements to include the complete range of solid solutions.…”
Section: Introductionmentioning
confidence: 99%